Selecting a vibration diagnostic defect 'Mechanical weakening of a structure'; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Ermolaev A. V. Andrey Vladimirovich (Mechanical Engineering Processes and Metal Treatment, 2016)
Title screen